Conceptual Framework for Fintech in Sharia Financial Planning - Masmuh, Muhammad Mukti Arif; Rahmawati, Rahmawati; Fahmi, Muhammad (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
Islamic financial planning is vital for individuals and financial institutions for a few reasons. In order to improve the role of Islamic financial planning as sustainable economic development for individuals and institutional, thus, the use of technology is needed. This research aims to develop a model framework with the purpose of an improvement in the usage of financial technology for Islamic financial planning.